First insight of the genome-wide association study and genomic prediction into enteritis disease (Vibrio harveyi) resistance trait in the lined seahorse (Hippocampus erectus) - Li, Siping; Liu, Xin; Shen, Fengyuan; Lin, Tingting; Zhang, Dong (Frontiers in Immunology, 2024)
Enteritis caused by Vibrio is a highly die-offs disease that severely impeded substantial production in seahorses aquaculture. We intend herein to investigate the genetic architecture firstly by genome-wide association study (GWAS) analysis, as well as to evaluate the feasibility of genomic selection (GS) in enteritis disease resistance trait of the lined seahorse Hippocampus erectus. Generally, challenged with LD50 of concentration of Vibrio harveyi, a total of 161 of susceptible and 166 of resistant individuals were allocated into binary survival phenotypes to perform with a GWAS analysis. Results indicated that the heritability for resistance to Vibrio harveyi was estimated to be 0.10. And a set of 10 significant/suggestive SNPs in a multiple chromosomes localization were identified, explaining 7.76% to 13.28% of genetic variance. Associated 82 of candidate genes were clustered into signal transduction, cell proliferation, response of external stress, bacteria defence, and anti-inflammatory processes. Moreover, the potential performance of genomic selection (GS) in application in selective breeding for enteritis disease resistance seahorses was assessed by genomic prediction (GP). In general, the predictive accuracy of the genomic estimated breeding value (GEBV) of BayesC exceeded the rrBLUP, BayesA, RKHS, and SVM models while with no significant difference. And the GWAS-informative SNPs was significantly superior in efficience than random selected markers by comparison of predictive performance on different selection strategies of SNPs. Overall, the genetic basis of enteritis disease resistance trait in the lined seahorse is a polygenic genetic architecture. SNPs associated with the important genes of cathepsin L1-like previously reported with respect to disease resistance are consider as potential molecular markers of genetic breeding. Furthermore, GS approach is an appropriate, effective, and less-cost application in breeding enteritis disease-resistant seahorses.